Respon Tekanan Transient Pada Reservoir Gas Multilayer Dengan Hydraulic Fracturing - M. Mahlil Nasution; Nugroho Marsiyanto; Citra Wahyuningrum (Jurnal Bhara Petro Energi, 2023)
Transient pressure analysis is designed to provide a quantitative analysis of reservoir properties. The data from the test results are collected to support information on a reservoir which is then used to become a predictive model and update the geological model. Based on the type, Pressure Transient is divided into pressure Build up and Pressure Drawdown. In testing, Pressure Transient analysis can describe the characteristics of the reservoir properties or the formation's ability to produce fluid. This test has advantages compared to other techniques in determining reservoir characteristics, because the transient pressure test covers a larger area so that it allows estimation of porosity, reservoir permeability, average pressure, skin, fracture length, reservoir heterogeneity, drainage area, shape, and even distance. can reach up to the boundary or flow discontinuities.